THE EFFECT OF SELENIUM ON PROPER BODY FUNCTION IN HORSES - A. Wyganowska; K. Górski; B. Jania; A. Danielewicz; K. Andraszek (Journal of Animal and Plant Sciences, 2017)
Due to selenium deficiencies commonly occurring in Europe, horse breeders must supplement the animals’ diet with this element. However, it is essential to know the level of selenium in the feed and in the animal tissues. The aim of the study was to determine and compare the serum content of selenium in horses in relation to the feeding season. The horses were used for recreation and sport. Blood was collected from the jugular vein into sterile test tubes without coagulant. In the mares that did not receive selenium supplements, a very low serum level of selenium was observed. The values were far below the norms established for horses (100 µg/l -200 µg/l) and ranged from 20 µg/l to 38 µg/l. The level of selenium in the mares which received pure selenium or selenium in the form of mineral preparations ranged from 56 µg/l to 85 µg/l. However, this level is still below the reference values. The geldings that received selenium, mineral and vitamin supplements and special feed had an appropriate level of selenium in the blood. The horses that did not receive selenium as a supplement had a low level of selenium, well below the norm.
Keywords: Disease; Horse; Nourishment; Selenium